Stakeholder Perspectives on the Official Administrative and Formation of Water User Associations in Kurdistan Province, Iran - Madine Osmanpour; Farzad Eskandari; Nazim Nariman; Shuokr Aziz (Advances in Civil Engineering and Environmental Science)
This research examines stakeholder perceptions of malpractices among administrative and affiliated departments in Kurdistan Province, Iran, and water users' willingness to establish Water User Associations (WUAs). The statistical population includes groundwater users, consisting of 10,091 individuals with profound and semi-deep well licenses, 394 individuals with applications for replacement wells, and 1,804 individuals with unauthorised wells. A stratified sampling method was applied to obtain a representative sample. Using Cochran's formula, the estimated sample sizes were 1,700 for the first group, 75 for the second, and 300 for the third. Qualitative data were gathered through a questionnaire and analyzed using SPSS. Expert opinions were sought to validate the research tool, and reliability was confirmed by calculating Cronbach's alpha after a pre-test. The results revealed moderate satisfaction with administrative services and case handling but dissatisfaction with the official organization. Approximately 75% of water users believe the water authority is the most capable entity to control and oversee groundwater protection and use. No significant differences were found in the perspectives of users from different regions regarding selecting an appropriate group to oversee groundwater resource management.